2018
DOI: 10.3892/br.2018.1101
|View full text |Cite
|
Sign up to set email alerts
|

Potential candidate treatment agents for targeting of cholangiocarcinoma identified by gene expression profile analysis

Abstract: Cholangiocarcinoma (CCA) remains to be a major health problem in several Asian countries including Thailand. The molecular mechanism of CCA is poorly understood. Early diagnosis is difficult, and at present, no effective therapeutic drug is available. The present study aimed to identify the molecular mechanism of CCA by gene expression profile analysis and to search for current approved drugs which may interact with the upregulated genes in CCA. Gene Expression Omnibus (GEO) was used to analyze the gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…A study of liver hepatocellular carcinoma (HCC) reported high levels of BIRC5 expression in HCC compared with the present study, which reported the downregulation of BIRC5 in EBV-transformed BLCL (41). TROAP was found to be upregulated in cholangiocarcinoma (42); however, the present study reported a downregulation of TROAP expression in EBV-transformed BLCL. These findings indicate that each pathogen has an independent ability to alter cellular gene expression that transforms normal cells into immortalized cells and causes cancer progression.…”
Section: Discussioncontrasting
confidence: 89%
“…A study of liver hepatocellular carcinoma (HCC) reported high levels of BIRC5 expression in HCC compared with the present study, which reported the downregulation of BIRC5 in EBV-transformed BLCL (41). TROAP was found to be upregulated in cholangiocarcinoma (42); however, the present study reported a downregulation of TROAP expression in EBV-transformed BLCL. These findings indicate that each pathogen has an independent ability to alter cellular gene expression that transforms normal cells into immortalized cells and causes cancer progression.…”
Section: Discussioncontrasting
confidence: 89%
“…As displayed in Table S1 , CHEK1 was the most significant upregulated gene. A published research has shown that CHEK1 is an important factor related to DNA replication and cell survival in cancer cells [ 21 ], and executes the function of the biological regulating enzyme in CCA [ 22 ]. The expression data of CHEK1 were further extracted from the CCA-related microarray data GSE45001 and GSE77984 and box plots were drawn.…”
Section: Resultsmentioning
confidence: 99%
“…The determination of the molecular mechanism about tumorigenesis is very important for the diagnosis and treatment of cancer patients [ 24 ]. There is an urgent need to study the pathogenesis of intrahepatic cholangiocarcinoma and the knowledge gained may help us to develop new clinical treatment strategies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%